Recovery of pure MnSO4 by crystallization after separation of Fe(III) and Zn(II) from the reductive leaching solution of manganese dust containing Mn3O4 - Wen J.-X.; Nguyen T.N.H.; Lee M.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Manganese dust generated during the production of ferroalloys contains iron and zinc oxides together with other minor oxides. Pure manganese compounds can be recovered from the leaching solution of the manganese dust by removing the impure ions. In this work, sulfuric acid and ferrous sulfate were employed as leaching and reducing agents for the manganese oxides in the dust. First, the leaching conditions for complete dissolution of the manganese oxides were investigated by varying the concentration of sulfuric acid and ferrous sulfate, and pulp density. Second, after oxidizing Fe(II) to Fe(III) by hydrogen peroxide, Fe(III) was removed from the solution by three stages of counter current extraction with D2EHPA. Third, Zn(II) was removed by two stages of cross current extraction with Cyanex 272. Stripping conditions for Fe(III) and Zn(II) were determined from the respective loaded organics. Fourth, Mn(OH)2 was precipitated from the raffinate by adjusting the pH of the solution to 10 with NaOH solution. The MnSO4 crystals with 99.5% purity were recovered by crystallization from the sulfuric acid solutions after the precipitates of Mn(OH)2 were dissolved. A comparison of the cost of the chemicals used to recover MnO2 and MnSO4 indicated that the current process was much more economical.